Enforcing ATP hydrolysis enhanced anaerobic glycolysis and promoted solvent production in Clostridium acetobutylicum - Dai, Zongjie (Microb Cell Fact, 2021)
BACKGROUND: The intracellular ATP level is an indicator of cellular energy state and plays a critical role in regulating cellular metabolism. Depletion of intracellular ATP in (facultative) aerobes can enhance glycolysis, thereby promoting end product formation. In the present study, we examined this s trategy in anaerobic ABE (acetone-butanol-ethanol) fermentation using Clostridium acetobutylicum DSM 1731. RESULTS: Following overexpression of atpAGD encoding the subunits of water-soluble, ATP-hydrolyzing F(1)-ATPase, the intracellular ATP level of 1731(pITF(1)) was significantly reduced compared to control 1731(pIMP1) over the entire batch fermentation. The glucose uptake was markedly enhanced, achieving a 78.8% increase of volumetric glucose utilization rate during the first 18 h. In addition, an early onset of acid re-assimilation and solventogenesis in concomitant with the decreased intracellular ATP level was evident. Consequently, the total solvent production was significantly improved with remarkable increases in yield (14.5%), titer (9.9%) and productivity (5.3%). Further genome-scale metabolic modeling revealed that many metabolic fluxes in 1731(pITF(1)) were significantly elevated compared to 1731(pIMP1) in acidogenic phase, including those from glycolysis, tricarboxylic cycle, and pyruvate metabolism; this indicates significant metabolic changes in response to intracellular ATP depletion. CONCLUSIONS: In C. acetobutylicum DSM 1731, depletion of intracellular ATP significantly increased glycolytic rate, enhanced solvent production, and resulted in a wide range of metabolic changes. Our findings provide a novel strategy for engineering solvent-producing C. acetobutylicum, and many other anaerobic microbial cell factories. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12934-021-01639-7.